Dielectrophoresis Aligned Single-Walled Carbon Nanotubes as pH Sensors - Li, Pengfei (Biosensors (Basel), 2011)
Here we report the fabrication and characterization of pH sensors using aligned single-walled carbon nanotubes (SWNTs). The SWNTs are dispersed in deionized (DI) water after chemical functionalization and filtration. They are deposited and organized on silicon substrates with the dielectrophoresis process. Electrodes with “teeth”-like patterns—fabricated with photolithography and wet etching—are used to generate concentrated electric fields and strong dielectrophoretic forces for the SWNTs to deposit and align in desired locations. The device fabrication is inexpensive, solution-based, and conducted at room temperature. The devices are used as pH sensors with the electrodes as the testing pads and the dielectrophoretically captured SWNTs as the sensing elements. When exposed to aqueous solutions with various pH values, the SWNTs change their resistance accordingly. The SWNT-based sensors demonstrate a linear relationship between the sensor resistance and the pH values in the range of 5–9. The characterization of multiple sensors proves that their pH sensitivity is highly repeatable. The real-time data acquisition shows that the sensor response time depends on the pH value, ranging from 2.26 s for the pH-5 solution to 23.82 s for the pH-9 solution. The long-term stability tests illustrate that the sensors can maintain their original sensitivity for a long period of time. The simple fabrication process, high sensitivity, and fast response of the SWNT-based sensors facilitate their applications in a wide range of areas.